PERAN CUSTOMER RELATION MANAGEMENT ( CRM ) DALAM MEMPENGARUHI LOYALITAS PELANGGAN (Studi Pada Pelanggan AUTO 2000 Cabang Sutoyo Malang) - Yenli Alfiah Permatasari; Ananda Sabil Hussein (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to determine the effect Customer Relation Management on Customer Loyality (Studies in AUTO 2000’s Customer Sutoyo Branch). Types of research used in this research is explanative research that aims to explain the causal relationship between the causal variables through hypothesis testing. The sampling technique used was nonprobability sampling and obtained a sample of 150 respondens in total. To test the hypothesis proposed in this study used classical assumption, validity, reliability, determination, and regression analysis. Regression analysis showed that indentify, differentiation, interaction,and customize as well as have a significant influence on customer loyalty. Based on these results, Auto 2000 can make indentify, differentiation, interaction,and customize as reference in predicting how good Customer Relation Management in AUTO 2000. Keywords: indentify, differentiation, interaction,and customize, Customer Relation Management